Derivational Suffixes Function Analysis in BBC News: War in Gaza - Jayanti, Ni Luh Putu Laras; I.G.B. Wahyu Nugraha Putra (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2025)
The aims of this research is focusing to identify of the function of the derivational suffixes found in the BBC News: “War in Gaza”. Descriptive qualitative methods were used to identify the explanation about the function of derivational suffixes that found. The theories from Katamba (1994) and McCarthy (2002) were used to analyze the data. The news from BBC News: “War in Gaza” were used. Based on the analysis, this study found 202 data of suffixes that categorized as class changing and class maintaining. The suffixes that changing the word class found in this study were found 120 (62%) data of noun derived from verb, 11 (6%) data of adjective derived from verb, 20 (10%) data of adjective derived from noun, 9 (5%) data of noun derived from adjective and 33 (17%) data of adverb derived from adjective. It was found many nouns derived from verb suffix in the class changing because based on McCarthy, suffix -er is the most common way to form the noun. Meanwhile the suffix that maintaining the word class, it was found 9 (4%) data. It was only from noun derived from noun because the suffixes are commonly used in the news.